Particularities of Solving the Problems of Support for Managerial Decision Making in Production and Economic Systems Using the Statistical Data - Mylnikov, Leonid A. (International Journal of Economics and Financial Issues, 2016)
The subject of this paper is the decision making processes in production and economic systems conditioned by implementation of goods innovation projects as well as economic and mathematical models and methods of managing the processes. The research object viewed in the paper is the construction of models of goods innovation projects implementation and the ways of implementation thereof based on the mathematical apparatus and statistical data. The paper discusses a method of constructing the models of support for managerial decision making in production and economic systems and working with them based on simulation and mathematical programming methods. The task of selecting the production and economic systems for implementation of projects as well as of forming the production and economic system portfolios is worded in general. The author also pays attention to the questions of designing and using the information systems based on simulation approaches for supporting the decision making, studying the goods innovation projects at various development stages, and the production and economic systems implementing them. A method of forming and transferring data is suggested the implementation of which will allow solving the tasks of support for decision making in production and economic systems based on statistical data and criterial methods as well as perform risk assessment and measure the sensitivity of the results obtained to changing characteristics of the projects and the influence of the environment. Keywords: decision making support; mathematical programming; volume scheduling; innovation project; production and economic system; data processing; statistical data. JEL Classifications: C44, C55, C63, C87